1994
DOI: 10.1038/bjc.1994.306
|View full text |Cite
|
Sign up to set email alerts
|

Centralised treatment, entry to trials and survival

Abstract: S_.mary A review was carried out of the published literature on survival rates for cancer in relation to patterns of organisation of medical care, specifically treatment at specialist centres or at hospitals treating larger numbers of patients and treatment by protocol, usually within the context of a clinical trial. Centralised referral or entry to trials was frequently associated with a higher survival rate, particularly for the less common cancers, and was never found to be associated with a lower survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
2
11

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(113 citation statements)
references
References 72 publications
2
98
2
11
Order By: Relevance
“…This 'trial effect', also known as the 'Hawthorn effect', has been explored in at least four systematic reviews (Stiller, 1994), (Braunholtz et al, 2001), (Peppercorn et al, 2004), (Vist Gunn et al, 2008). Although their conclusions differ regarding as to the extent to which trials actually have benefit, all these authors agree that it is more likely that trials have a positive than negative effect on the outcomes for those taking part.…”
Section: Self-interest Is a Key Motive For Participatingmentioning
confidence: 99%
“…This 'trial effect', also known as the 'Hawthorn effect', has been explored in at least four systematic reviews (Stiller, 1994), (Braunholtz et al, 2001), (Peppercorn et al, 2004), (Vist Gunn et al, 2008). Although their conclusions differ regarding as to the extent to which trials actually have benefit, all these authors agree that it is more likely that trials have a positive than negative effect on the outcomes for those taking part.…”
Section: Self-interest Is a Key Motive For Participatingmentioning
confidence: 99%
“…Therapy Three measures covering surgery, radiotherapy, and chemotherapy were used, that is, the proportions of new breast cancer patients who received conservation surgery; in whom conservation surgery was followed by radiotherapy; and who were Clinical innovation Three measures were used: that is, who were aged under 70 years, and received induction chemotherapy; entered patients into any of nine open national clinical trials (Stiller, 1989(Stiller, , 1994; routinely measured oestrogen receptor status.…”
Section: Measures Usedmentioning
confidence: 99%
“…However, survival and, by extension, mortality may also be influenced by the organisation and availability of cancer diagnosis and treatment facilities. Studies have suggested that patients treated at specialist centres or teaching hospitals may have improved prognosis (Stiller, 1994;Harding et al, 1993;Gillis et al, 1991;Karjalainen, 1990). The use of treatment protocols, both within and outwith clinical trials (Karjalainen and Palva, 1989) and treatment by a specialist (Junor et al, 1994;McArdle and Hole, 1991) have been shown to increase survival.…”
Section: Resultsmentioning
confidence: 99%